Cognitive and behavioral therapy for insomnia increases the use of continuous positive airway pressure therapy in obstructive sleep apnea participants with comorbid insomnia: a randomized clinical trial. Issue 12 (12th August 2019) - Sweetman, Alexander; Lack, Leon; Catcheside, Peter G; Antic, Nick A; Smith, Simon; Chai-Coetzer, Ching Li; Douglas, James; O'grady, Amanda; Dunn, Nicola; Robinson, Jan; Paul, Denzil; Williamson, Paul; et al.
Abstract: Study Objectives: Insomnia and obstructive sleep apnea (OSA) commonly co-occur which makes OSA difficult to treat with continuous positive airway pressure (CPAP). We conducted a randomized controlled trial in participants with OSA and co-occurring insomnia to test the hypothesis that initial treatment with cognitive and behavioral therapy for insomnia (CBT-i), versus treatment as usual (TAU) would improve insomnia symptoms and increase subsequent acceptance and use of CPAP. Methods: One hundred and forty-five participants with OSA (apnea-hypopnea index ≥ 15) and comorbid insomnia were randomized to either four sessions of CBT-i, or TAU, before commencing CPAP therapy until 6 months post-randomization. Primary between-group outcomes included objective average CPAP adherence and changes in objective sleep efficiency by 6 months. Secondary between-group outcomes included rates of immediate CPAP acceptance/rejection, and changes in; sleep parameters, insomnia severity, and daytime impairments by 6 months. Results: Compared to TAU, participants in the CBT-i group had 61 min greater average nightly adherence to CPAP (95% confidence interval [CI] = 9 to 113; p = 0.023, d = 0.38) and higher initial CPAP treatment acceptance (99% vs. 89%; p = 0.034). The CBT-i group showed greater improvement of global insomnia severity, and dysfunctional sleep-related cognitions by 6 months (both: p < 0.001), and greater improvement in sleep impairment measures immediately following CBT-i. There were no between-group differences in sleep outcomes, or daytime impairments by 6 months. Conclusions: In OSA participants with comorbid insomnia, CBT-i prior to initiating CPAP treatment improves CPAP use and insomnia symptoms compared to commencing CPAP without CBT-i. OSA patients should be evaluated for co-occurring insomnia and considered for CBT-i before commencing CPAP therapy. Clinical Trial: Treating comorbid insomnia with obstructive sleep apnea (COMSIA) study: A new treatment strategy for patients with combined insomnia and sleep apnea, https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=365184 Australian New Zealand Clinical Trials Registry: ACTRN12613001178730. Universal Trial Number: U1111-1149-4230.